2016
DOI: 10.1044/2016_ajslp-15-0133
|View full text |Cite
|
Sign up to set email alerts
|

Use of tDCS in Aphasia Rehabilitation: A Systematic Review of the Behavioral Interventions Implemented With Noninvasive Brain Stimulation for Language Recovery

Abstract: A review of the behavioral treatments implemented in tDCS aphasia rehabilitation studies highlights several methodological considerations for future investigations. Impairment-focused and pragmatic treatments have been implemented in tDCS aphasia research studies. No one behavioral approach stands out as the best treatment to combine with tDCS for the promotion of language recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Transcranial direct current stimulation (tDCS) is proposed as an economical and non-invasive method of enhancing recovery after stroke when paired with behavioural training [1][2][3][4][5][6][7][8][9][10]. However, the effects of tDCS vary substantially across individuals [11,12] making adoption into routine clinical practice difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial direct current stimulation (tDCS) is proposed as an economical and non-invasive method of enhancing recovery after stroke when paired with behavioural training [1][2][3][4][5][6][7][8][9][10]. However, the effects of tDCS vary substantially across individuals [11,12] making adoption into routine clinical practice difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we placed electrodes over 10-05 coordinates Fp2 and CCP3 for both participants. For the other montage, often used in aphasia rehabilitation studies[7,8] to target BA44, the anode is positioned over left frontal cortex (BA44) and the…”
mentioning
confidence: 99%
“…As results of the acute neurological events related to COVID-19 infection, functional outcomes of patients surviving an ICU admission report also a high prevalence of speech, language and cognitive-communication disorders (Avula et al, 2020). tDCS has been previously applied concurrently with speech therapy for language recovery in aphasia (Galletta et al, 2016;Fridriksson et al, 2018Fridriksson et al, , 2019.…”
Section: Role In Post-acute Recovery Of Functionmentioning
confidence: 99%
“…But only a few studies have investigated whether the positive effect may be further enhanced by combining excitatory stimulation of the left hemisphere and inhibitory stimulation of the right hemisphere. Existing studies (Lee et al, 2013;Marangolo et al, 2016) have found positive effects of such bilateral stimulation. However, to the best of our knowledge, no studies have used both necessary control conditions, testing whether the effect of bilateral stimulation is superior to both excitatory stimulation of the left hemisphere only and to inhibitory stimulation of the right hemisphere only.…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a safe and tolerable brain stimulation method that has a high potential for routine clinical use to increase the gains of behavioral aphasia treatment (Galletta et al, 2016). However, it remains largely unknown which stimulation settings and targets provide the greatest therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%